Knowledge Action Repertoires and the Outcomes of Collective Action: Local Community Action for Environmental Protection - Parks, Louisa (PARTECIPAZIONE E CONFLITTO, 2021)
The article uses the knowledge practice repertoire approach, combined with an integrated opportunity approach, to investigate the role that local community knowledge based on holistic worldviews plays in the formation of collective actors, action and outcomes. This is argued to be crucial given that environmental governance is shaped instead by knowledge based on a worldview of a nature/culture divide, and that local community knowledge is key to responding to the planetary crisis and subject to this potential ontological clash. Attention to local community collective action using this lens can shed light on whether and how spaces can be made for different approaches, giving a fresh view to how outcomes matter. The article presents two case studies of local community collective action through community protocols from South Africa and Argentina. Community protocols are documents, recognised in international environmental law, where local communities set out their worldviews, their traditional knowledge and practices in support of environmental protection, and link these to rights and protections in national and international law as a basis for collective action. They are thus ideal sites for investigating knowledge practices and ontological politics. Focusing on different types of knowledge practices and opportunity contexts helped to untangle the complex question of how outcomes mattered to the local communities in these cases.